The influence of the relative position of the thiophene and pyrrole rings in donor-acceptor thienylpyrrolyl benzothiazole derivatives. A photophysical and theoretical investigation - Pina, João (2010)
A detailed spectroscopic and photophysical study has been carried out on a series of heterocyclic compounds -known to display nonlinear optical properties- consisting on one electron donating thienylpyrrolyl π-conjugated system functionalized with an electron acceptor benzothiazole moiety. The absorption, emission and triplet-triplet absorption together with all relevant quantum yields (fluorescence, intersystem crossing and internal conversion), excited state lifetimes and the overall set of deactivation rate constants (kF, kIC and kISC) were obtained in solution at room (293 K) and low (77 K) temperature. The optimized ground-state molecular geometries for the compounds together with the prediction of the lowest vertical one-electron excitation energy and the relevant molecular orbital contours for the compounds were also determined using the density functional theory (DFT) at the B3LYP/3 21G* level. The experimental results showed that the photophysical properties are influenced by the relative position of the pyrrole and thiophene relative to the benzothiazole groups.